(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The presence of Cerodontha (Poemyza) unisetiorbita Zlobin, mining on Phyllostachys mitis A. et C. Riviére, has been recorded. It is believed that the insect has been in Italy for many years, because some specimens have been caught in different places, very distant from each other. The most important morphological and biological characteristics are given.